2012
DOI: 10.1177/0091552112456281
|View full text |Cite
|
Sign up to set email alerts
|

Students With Disabilities at 2-Year Institutions in the United States

Abstract: This study used data from the Beginning Postsecondary Students Longitudinal Study to examine the demographic and in-college characteristics of students with disabilities at 2-year institutions, identify the types of educational services available to them, and determine how students’ disability conditions and their selected demographic and in-college characteristics related to their persistence. Nearly 25% of the students with disabilities in the sample did not persist beyond their first year, and almost 51% le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 31 publications
2
56
0
Order By: Relevance
“…Future research. Younger age was related to two components of intention to graduate among students, a finding consistent with some studies Mamiseishvili and Koch, 2012) but not others (O'Neill, et al, 2012). The literature suggests that some students wait before starting postsecondary studies, and it is these students' older age that is related to drop-out (Mamiseishvili and Koch, 2011).…”
Section: When Do Students Drop-outsupporting
confidence: 86%
See 2 more Smart Citations
“…Future research. Younger age was related to two components of intention to graduate among students, a finding consistent with some studies Mamiseishvili and Koch, 2012) but not others (O'Neill, et al, 2012). The literature suggests that some students wait before starting postsecondary studies, and it is these students' older age that is related to drop-out (Mamiseishvili and Koch, 2011).…”
Section: When Do Students Drop-outsupporting
confidence: 86%
“…For example, Mamiseishvili and Koch (2012) showed that almost 51% of students with disabilities in two-year institutions had left their studies by the end of their third year. On the other hand, O 'Neill, Markward, and French (2012) found that of those no longer enrolled, 74% of university students with disabilities had graduated.…”
Section: Persistence and Drop-out Among Postsecondary Students With Dmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of preparedness may cultivate a lack of self-confidence in students with a visual impairment, hindering their ability to adapt academically and psychosocially to college (Eckes & Ochoa, 2005;Gartin et al, 1996;Reed & Curtis, 2011;. As personalemotional adjustment is positively related to persistence at college (Kim et al, 2007;Mamiseishvili & Koch, 2012), staff at high schools should provide psychosocial support and services for students with a visual impairment before they move to higher education. This could be done by, for example, providing assertiveness training, courses to develop skills for coping with stress and depression, interaction skills, and skills in physical communication.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these studies have demonstrated that, academic and social integration positively influence student learning, development, and likelihood of persistence (e.g., Boutin, 2008;Getzel, 2009 Mamiseishvili and Koch (2011) observed that in a national sample of college students with disabilities, on-campus living, full-time enrollment, degree expectations, first-year GPA, and net price of attendance predicted first-to-second-year persistence. In a related study, Mamiseishvili and Koch (2012) used the BPS:04/06 data set to examine factors related to both first-to-second and three-year cumulative persistence for students with disabilities enrolled at two-year postsecondary institutions. Their rationale for focusing exclusively on two-year institutional enrollment was that these institutions are often the entry point into higher education for students with disabilities.…”
Section: Research On Persistencementioning
confidence: 99%